1989
DOI: 10.1021/ie00086a001
|View full text |Cite
|
Sign up to set email alerts
|

Bulk free radical polymerization of styrene with unsymmetrical bifunctional initiators

Abstract: An experimental study of the bulk free radical polymerization of styrene catalyzed by thermally unsymmetrical bifunctional initiator 4-((tert-butylperoxy)carbonyl)-3-hexyl-6-[7-((tert-butylperoxy)carbonyl)heptyl] cyclohexene is reported. The cyclic peroxyester group and the primary peroxyester group in the bifunctional initiator molecule have significantly different thermal stabilities. When this unsymmetrical bifunctional initiator is used for styrene polymerization a t high temperatures, it is possible to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The characteristic linear increase of monomer conversions in thermal styrene polymerizations is related to the mild gel effect of styrene polymerizations . The increase of monomer conversion with temperature is related to the increase of rates of thermal initiation and propagation . The decrease of the average molar masses with the temperature increase is related to the faster increase of rates of chain termination, when compared with the rates of propagation.…”
Section: Resultsmentioning
confidence: 95%
“…The characteristic linear increase of monomer conversions in thermal styrene polymerizations is related to the mild gel effect of styrene polymerizations . The increase of monomer conversion with temperature is related to the increase of rates of thermal initiation and propagation . The decrease of the average molar masses with the temperature increase is related to the faster increase of rates of chain termination, when compared with the rates of propagation.…”
Section: Resultsmentioning
confidence: 95%
“…[17][18][19] However, this behavior was not observed for the bi-and trifunctional cyclic initiators used in this study, which indicated that there was no substantial difference in the reactivities of the two or three peroxide groups contained by initiator molecules under isothermal conditions. Another important feature was that there was no physical evidence of the gel effect in the temperature range of 90 -200°C and conversion range of 95-99%, in spite of it being demonstrated that termination reactions involving polymeric radicals became diffusion controlled and the termination rate constant decreased considerably with an increase in the monomer conversion.…”
Section: Polymerization Of Styrene In Presence Of Cyclic Dps and Tpsmentioning
confidence: 91%
“…Using polyethylene as an example, it has been found that size exclusion chromatography (SEC) can detect a minimum length for an alkane branch somewhere between six and twelve carbons 37,38. It is generally accepted that six carbons or longer can be detected by 13C NMR spectroscopy 39–41. In the case of rheological methods, a definite length has not been completely established.…”
Section: Characterizationmentioning
confidence: 99%
“…Since that time, there have been numerous studies expounding the behaviour of difunctional initiators and their benefits towards polymer production, with most of the focus on styrene monomer 9–22. It has been shown that through repeated initiation, propagation and termination steps, multifunctional initiators are able to generate high rates of polymerization while maintaining high molecular weights (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%